Political connections and corporate investments: Evidence from the recent anti-corruption campaign in China - Pan, Xiaofei; Tian, Gary Gang (Journal of Banking & Finance, 2020)
Taking advantage of corruption scandals in China, we construct a natural experiment and identify the ousting of corrupt politicians, and firms connected with them through bribery and personal relationships (event firms). We find that the investment expenditure of event firms declines significantly after the ousting of the politicians compared with that of non-event firms, especially for non-SOEs. We also find that, after the ousting of the politicians, investment efficiency improves for event SOEs, but declines for event non-SOEs, compared with their non-event counterparts. We also document that the ousting of the politicians influences firm investment decisions more after the recent anti-corruption campaign, for bribing firms and for firms in more corrupt regions. These results are robust to alternative measurements of key variables and specifications.